Feasibility of ternary gas mixture containing SF6: an overview - Noor Mazliza, Noor Mazliza; Muhammad Saufi, Muhammad Saufi (Penerbit UTHM, 2020)
Recently, the search for a suitable replacement of SF6 is running towards the environmental concerns due to its powerful greenhouse gas (GHG). Its global warming potential (GWP) is approximately 23,500 times greater than of CO2 for a given 100-years’ time horizon. Up to now, there is still an unclear solution for SF6 alternative gases considering these environmental issues. A candidate to partially or entirely replace SF6 gas for power industry should deliver the same benefits as SF6. Its affinity to electron, called as electronegativity probably makes SF6 the most attractive overall gaseous insulation in electrical apparatus [1].